2022
DOI: 10.1002/acn3.51700
|View full text |Cite
|
Sign up to set email alerts
|

Percentage brain volume change in multiple sclerosis mainly reflects white matter and cortical volume

Abstract: Brain atrophy in multiple sclerosis (MS), as measured by percentage brain volume change (PBVC) from brain magnetic resonance imaging (MRI), has been established as an outcome parameter in clinical trials. It is unknown to what extent volume changes within different brain tissue compartments contribute to PBVC. We analyzed pairs of MRI scans (at least 6 months apart) in 600 patients with relapsing–remitting MS. Multiple regression revealed that PBVC mainly reflects volume loss of white and cortical gray matter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The chronic and progressive inflammation of myelin and nerve fibers results in continuing brain volume loss. A large (600 patients) retrospective cohort study showed that percentage brain volume change mainly reveals the loss of white and cortical gray matter [ 6 ]. Simultaneous volumetric analysis shows that in patients with multiple sclerosis, choroid plexuses are substantially bigger than healthy controls [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The chronic and progressive inflammation of myelin and nerve fibers results in continuing brain volume loss. A large (600 patients) retrospective cohort study showed that percentage brain volume change mainly reveals the loss of white and cortical gray matter [ 6 ]. Simultaneous volumetric analysis shows that in patients with multiple sclerosis, choroid plexuses are substantially bigger than healthy controls [ 7 ].…”
Section: Introductionmentioning
confidence: 99%